Unravelling substitution effects on charge transfer characteristics in cocrystals of pyrene based donors and 3, 5-dinitrobenzoic acid. Issue 29 (8th July 2019) - Mandal, Arkalekha; Rissanen, Kari; Mal, Prasenjit
Abstract : Ambipolar to p-type semiconductivity switching with the change of the ⋯DADADA⋯ to ⋯ADDADD⋯ packing arrangement in charge transfer cocrystals of pyrene based donors is discussed. Abstract : Here we report charge-transfer cocrystals composed of pyrene and amino/bromopyrene as π-donors (D) and 3, 5-dinitrobenzoic acid (A) as a π-acceptor. The 1 : 1 cocrystals of pyrene/1-aminopyrene adopt a ⋯DADADA⋯ mixed stack arrangement whereas the 2 : 1 cocrystal of 1-bromopyrene and 3, 5-dinitrobenzoic acid shows ⋯DDADDA⋯ stacking. Crystallographic, spectral and theoretical studies reveal that the frontier molecular orbital energy level rather than the π-donor strength plays the governing role in predicting charge transfer. In addition, a theoretical study demonstrates that the ambipolar semiconductor nature in cocrystals of the pyrene/aminopyrene donor and the p-type nature of bromopyrene with the 3, 5-dinitrobenzoic acid acceptor are governed solely by the supramolecular structure and not by other factors.